1998
DOI: 10.1111/j.1432-2277.1998.tb00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the surgical technique on long-term outcome of pancreas transplantation

Abstract: To date there is no general consensus as to the best surgical technique for pancreas transplantation. Patients with a pancreas transplant functioning for 3 years or more were retrospectively investigated to compare three surgical techniques: segmental graft with duct obstruction (DO), whole graft with bladder drainage (BD), and whole graft with enteric drainage (ED). Several parameters were studied: patient and graft survival, rejection, long-term surgical and medical complications, and endocrine function. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In our cohort of patients, an identical proportion of patients in the SC and NSC groups were bladder-drained and entericdrained. There is no evidence in the literature to suggest that either technique reduces surgical complications, but some studies have shown improved graft survival for bladderdrained grafts [25,35], others for enteric-drained grafts [38] and some have shown no difference in graft survival between the two methods [26,36].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort of patients, an identical proportion of patients in the SC and NSC groups were bladder-drained and entericdrained. There is no evidence in the literature to suggest that either technique reduces surgical complications, but some studies have shown improved graft survival for bladderdrained grafts [25,35], others for enteric-drained grafts [38] and some have shown no difference in graft survival between the two methods [26,36].…”
Section: Discussionmentioning
confidence: 99%
“…190 Two recent long-term studies reported that >40% of patients with bladder drainage require enteric conversion at some point in time. 197,207 Additionally, bladder drainage increased the rate of metabolic and urologic complications, 188,198,[208][209][210][211][212][213][214][215][216] and did not improve immunologic outcome of either SPK 187,[190][191][192][196][197][198]205,206,208,214,217,218 or solitary pancreas transplantations. 70,171,219 Duodeno-duodenostomy (vs. duodeno-jejunostomy) was not considered to clearly increase the overall rate of surgical complications after pancreas transplantation, despite higher rates of bleeding.…”
Section: 2%mentioning
confidence: 99%